2020
DOI: 10.3390/vaccines8030556
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Immunization Services for Maternal and Infant Vaccines: Results of a Survey Conducted by Imprint—The Immunising Pregnant Women and Infants Network

Abstract: The COVID-19 pandemic response has caused disruption to healthcare services globally, including to routine immunizations. To understand immunization service interruptions specifically for maternal, neonatal and infant vaccines, we captured the local experiences of members of the Immunising Pregnant Women and Infants Network (IMPRINT) by conducting an online survey over 2-weeks in April 2020. IMPRINT is a global network of clinicians and scientists working in maternal and neonatal vaccinology. The survey includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 29 publications
4
87
1
Order By: Relevance
“…Consistent with evidence no COVID-19 and prior outbreaks, we found that fear of contracting COVID was a commonly reported reason for missed immunizations. [6,8,9,12] Public health policies will need to allay these fears by building trust in public primary care services, clearly communicating the importance of continuing immunizations even during a pandemic, and ensuring that attending immunization camps does not increase the risk of COVID infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with evidence no COVID-19 and prior outbreaks, we found that fear of contracting COVID was a commonly reported reason for missed immunizations. [6,8,9,12] Public health policies will need to allay these fears by building trust in public primary care services, clearly communicating the importance of continuing immunizations even during a pandemic, and ensuring that attending immunization camps does not increase the risk of COVID infection.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Travel and access barriers, supply-side disruptions due to provider shortages and suspended immunization services, and user fears of contracting COVID-19 have emerged as key reasons for reductions in immunizations. [8,9] Disruptions to routine and critical care during large disease outbreaks can have sizeable effects on health outcomes. Sharp decreases in health care utilization during the Ebola and SARS epidemics were estimated to have indirect mortality effects similar in magnitude to the direct effects of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…In LMICs, provider issues such as shortage of healthcare workers, closed vaccine clinics, suspension of vaccination services, and lack of personal protective equipment among health workers have been identified as barriers in vaccine delivery due to COVID-19. 29 These might lead to an increase in numbers of unimmunised or partially immunised children in community.…”
Section: Availability Of Vaccines and Healthcare Providersmentioning
confidence: 99%
“…Furthermore, logistical barriers towards access to vaccines were noticed, which seem to be amplified with a lack of vision and clear action plan about moving forward. 29 The ongoing pandemic was introduced as a novel and massive threat which led to creating much chaos and panic in the healthcare system across the world. Consequently, many countries have been looking up to WHO international guidelines as the resource towards safe continuation to regular vaccination.…”
Section: Management Approachesmentioning
confidence: 99%
See 1 more Smart Citation